A Negotiated Disadvantage? California Collective Bargaining Agreements and Achievement Gaps. (October 2021) - Marianno, Bradley D.
Using panel data from three successive collective bargaining (CBA) negotiation cycles from 277 California school districts in a difference-in-differences framework, I investigate the relationship between changes in CBA restrictiveness and racial and economic achievement gaps over time. I find that achievement gaps in California are smaller where contracts increase in restrictiveness in class size and larger where contracts increase in restrictiveness in teacher evaluation and leave policies over time, though this is not the case for all student subgroups. These effects are primarily concentrated in math, are small in magnitude, and are sometimes delayed in their timing. Altogether, this study provides some evidence that contract changes are associated with the educational opportunities of school districts' diverse and economically disadvantaged students.